Design of a low-cost virtual reality system, as an aid mechanism in online classes for children - Auccahuasi, Wilver (2021)
In the development of educational activities, being able to understand and understand the activities carried out is important to be able to have the greatest concentration, many techniques use audio-visual educational material. Taking advantage of this material in the present work a methodology is proposed to be able to use this material using low-cost devices, in order to have a virtual reality system with all the functionalities and with a control where the development of the material that is being displayed can be monitored. as well as being able to manage the material. The methodology proposes the use of virtual reality glasses the size for children, a cell phone, a computer and a wireless network, accompanied by a virtual reality program that can be configured and connected between a computer, this configuration is done using the application “Trinus VR”, which allows us to connect and share the visualization between the computer and the cell phone. In the application of the methodology, it was visualized with some stories where children can read and understand the message of the story, the results show that children can concentrate better if they are shown audiovisual material and through virtual reality glasses maximum concentration is achieved Because he is only looking at the story, likewise the use of virtual reality glasses of the size for children, helps the child feel comfortable and does not perceive the use of the glasses, achieving only focus on the story, we conclude by indicating that the methodology can be scalable and applicable to other courses and disciplines.